Dexmedetomidine as a Primary Sedative Agent after Single‐Stage Airway Reconstruction. Issue 3 (4th January 2013) - McCormick, Michael E.; Johnson, Yewande J.; Pena, Maria; Wratney, Angela T.; Pestieau, Sophie R.; Zalzal, George H.; Preciado, Diego A.
Abstract : Objective: To examine the outcomes of children receiving dexmedetomidine after single‐stage airway reconstruction. Study Design: Historical cohort study. Setting: Tertiary care children's hospital. Subjects and Methods: Of 61 eligible patients, 50 children undergoing single‐stage airway reconstruction were included in the study. Thirty children received dexmedetomidine (Dex) as a primary sedative agent, and 20 received a more traditional sedation protocol (no Dex). Primary outcomes included complications, intubation lengths, and lengths of pediatric intensive care unit (PICU)/hospital admission. Secondary analysis incorporating polypharmacy and age was performed using multivariate linear regression models. Results: Median age was 18.0 months. Age, sex, and weight were similar between the groups. Intubation length was equal in the 2 groups, and there were no statistical differences between lengths of PICU or hospital stay after extubation. Similarly, overall and individual complications were all similar, and there was no difference between the 2 groups in the amount of polypharmacy administered. On multivariate analysis, polypharmacy and younger age were independently correlated with an increase in overall complications, and polypharmacy alone was correlated with an increased length of stay after extubation. Conclusion: The use of dexmedetomidine as a primary sedation agent after single‐stage airway surgery does not appear to improve outcomes or decrease the need for additional pharmacologic agents. Polypharmacy was associated with an increase in overall complications and an increased length of stay after extubation. Although success can be expected in greater than 90% of these surgical patients, the optimal postoperative sedation management remains challenging.